Retos de la ley de garantías mobiliarias en Colombia. (2015)
The law of secured transactions reached to Colombia, product generated by Doing Business report, in which it is included Colombia, about the business climate of our country, that is, what advantages could offer Colombia for investors. Hand to hand with this report are the provisions contained in the government plan of 2013, by which you want to achieve generation and increased employment in our country. Given this background, the idea of looking for alternatives to the attainment of these objectives, so a group formed by the top managers of regulatory bodies, among them, the Superintendence of Companies, Superintendence of Industry and Commerce, ministries and other partners, taking into account the concept of enterprise and the need to grow in our country, put their eyes on Secured Transactions Law, which has been used internationally and taking into account the excellent results and good experience from other countries, decided to analyze and implement the law, according to international standards and in accordance with the rules in commercial matters in Colombia. Among the most important principles, which were treated through the project of law 1676 of 2013, is the access to credit for micro, small and medium enterprises, which may have credit facilities, given that increases the amount of assets that may serve as collateral for credit operations. Similary, from a legal point of view, it seeks to redesign the concept of security, unify and systematiz them based on the principles of priority, enforceability and economics.